The ecological approach to cognitive–motor dual-tasking: findings on the effects of expertise and age - Schaefer, Sabine (Frontiers in Psychology, 2014)
The underlying assumption of studies on cognitive–motor dual-tasking is that resources are limited, and when they have to be shared between a cognitive and a motor task, performances will suffer. Resource competition should therefore be particularly pronounced in children, older adults, or people who are just acquiring a new motor skill. The current review summarizes expertise and age comparative studies that have combined a cognitive and a motor task. Expertise studies have often assessed sports performances (e.g., golf putting, soccer dribbling, rugby drills) and have shown that experts are more successful than novices to keep up their performances in dual-task situations. The review also presents age-comparative studies that have used walking (on narrow tracks or on a treadmill) as the motor task. Older adults often show higher costs than young adults, and they tend to prioritize the motor domain. These findings are discussed in relation to the ecological approach to dual-task research originally introduced by K. Z. H. Li, Krampe, and Bondar (2005). The approach proposes to study ecologically valid dual-task situations, and always to investigate dual-task costs for both domains (cognitive and motor performance) in order to assess potential tradeoffs. In addition, task difficulties should be individually adjusted, and differential-emphasis instructions should be included in the study design.